Meta-analysis of structural and functional alterations of brain in patients with attention-deficit/hyperactivity disorder - Yu, Miaomiao; Gao, Xinyu; Niu, Xiaoyu; Zhang, Mengzhe; Yang, Zhengui; Han, Shaoqiang; Cheng, Jingliang; Zhang, Yong (Frontiers in Psychiatry, 2023)
Background: A large and growing body of neuroimaging research have concentrated on patients with ADHD, but with inconsistent conclusions. This article was intended to explore the common and certain neural alterations in structure and function in ADHD, further explore the differences in brain alterations between adults and children with ADHD. Methods: We conducted an extensive literature search of whole-brain voxels-based morphological and functional magnetic resonance imaging studies associated with ADHD. Two separate meta-analyses with the seed-based d mapping software package for functional neural activation and gray matter volume were carried out, followed by a joint analysis and subgroup analysis. Results: This analysis included 29 VBM studies, and 36 fMRI studies . Structurally, VBM analysis showed that the largest GM volume diminutions in ADHD patients were in the several frontal-parietal brain regions, limbic system, and corpus callosum. Functionally, fMRI analysis discovered that significant hypoactivation in the several frontal-temporal brain regions, right postcentral gyrus, left insula and corpus callosum. Conclusion: This study showed that abnormal alterations in the structure and function of the left superior frontal gyrus and corpus callosum may be the key brain regions involved in the pathogenesis of ADHD patients, and which may be employed as an imaging metric for ADHD patients, pending future research. In addition, this meta-analysis also actually discovered neuroanatomical or functional abnormalities in other brain regions in ADHD, as well as findings that can be utilized to guide future research.